Upaya Peningkatan Pengetahuan tentang Infeksi Menular Seksual pada Remaja di SMAN 4 Palangka Raya - Permatasari, Silvani; Widayati, Ratna; Handayani, Septi (LPPM Universitas Palangka Raya, 2024)
Sexually Transmitted Infection (STI) is an infection triggered by bacteria, viruses, protozoa, parasites and fungi which is transmitted mainly through sexual contact, including anal and oral. Apart from that, STIs can also be transmitted through direct contact with contaminated objects, for example towels, sex toys, syringes, thermometers, and also through pregnant women to their fetuses or during the birth stage. One age group that is vulnerable to STIs is teenagers. Teenagers are more often encouraged to explore sexual experiences, which can increase the risk of experiencing STIs. One of the problems of teenagers at SMAN 4 Palangka Raya based on the results of interviews with students related to STI cases is the low level of knowledge about STIs. This service activity aims to increase teenagers' knowledge about STIs and spread this knowledge to the surrounding environment. The method used is a lecture containing material about the definition and meaning of STIs, the causes of STIs, symptoms caused by STI-causing agents in both men and women, how STIs are transmitted and how to prevent them. Service activities begin with socialization, implementation and evaluation of results. The implementation of Community Service activities in the form of efforts to increase knowledge about sexually transmitted infections in adolescents at SMAN 4 Palangka Raya was successful, participants enthusiastically listened to the material presented. There was a significant increase in knowledge after counseling compared to the pretest. Counseling can increase students' knowledge about the types of STIs and their complications.